2020
DOI: 10.1007/s40750-020-00141-5
|View full text |Cite
|
Sign up to set email alerts
|

Stereotypes and Structure in the Interaction between Facial Emotional Expression and Sex Characteristics

Abstract: Objective: A significant body of work has now amassed investigating the interaction between facial cues of sex and emotional expression. For instance, studies have found that male/more masculine faces are perceived more easily as angry, while female/more feminine faces are perceived more easily as happy. Two key mechanisms have been proposed to explain this interaction: a visualstructural account, where the interaction emerges due to physical overlap between facial cues of sex and emotion, and a stereotype bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 132 publications
(159 reference statements)
2
13
0
2
Order By: Relevance
“…Past studies have identified that interactions between sex and emotion can arise through multiple mechanisms including a contribution of bottom-up perceptual (visual structural overlap) and higher-order evaluative processes or stereotypic overlap between sex and emotion categories, or both (Becker et al, 2007; Bijlstra et al, 2010; Hugenberg & Sczesny, 2006; see Craig & Lee, 2020 for a review). For example, an angry expression on a male face may be recognized more efficiently than on a female face due to the bottom-up influence of masculine features such as an angular jaw and prominent brows accentuating an angry snarl (see Becker et al, 2007 for empirical evidence of this mechanism).…”
Section: Simple Categorizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Past studies have identified that interactions between sex and emotion can arise through multiple mechanisms including a contribution of bottom-up perceptual (visual structural overlap) and higher-order evaluative processes or stereotypic overlap between sex and emotion categories, or both (Becker et al, 2007; Bijlstra et al, 2010; Hugenberg & Sczesny, 2006; see Craig & Lee, 2020 for a review). For example, an angry expression on a male face may be recognized more efficiently than on a female face due to the bottom-up influence of masculine features such as an angular jaw and prominent brows accentuating an angry snarl (see Becker et al, 2007 for empirical evidence of this mechanism).…”
Section: Simple Categorizationmentioning
confidence: 99%
“…Further, where there is ambiguity, a person may incorrectly label the expression/category membership in line with the identified social biases. The interaction between the attributes of sex and emotion, has been the target of many studies (see Craig & Lee, 2020 for a review).…”
Section: Simple Categorizationmentioning
confidence: 99%
“…Por un lado, tanto el efecto de ventaja endogrupal en mujeres y la tendencia a exogrupal en hombres, podría atribuirse a algunos aspectos biológicos relacionados con el rol que ejercen en la crianza las mujeres (Baptista et al, 2017), sumados a ciertas diferencias morfológicas, hormonales y neuronales observadas en otros estudios (Craig & Lee, 2020;Kret & De Gelder, 2012;McDuff et al, 2017).…”
Section: Discusión Y Conclusionesunclassified
“…Otra variable que genera diferencia en el reconocimiento de expresiones de emoción es la edad; la habilidad de reconocer expresiones faciales de emoción se desarrolla en la infancia temprana y aumenta conforme la edad, hasta llegar a un punto máximo y comenzar a decaer apuntan a un posible efecto de ventaja endogrupal en mujeres, particularmente se ha encontrado que las mujeres tienen un desempeño mayor cuando el estímulo utilizado presenta mujeres emitiendo la emoción, sobre todo si pertenecen al mismo grupo racial (Craig & Lee, 2020). Considerando la variable de edad, Mestas et al (2015) encontraron que niños tenían un mejor desempeño decodificando emociones si el estímulo presentaba a un niño en lugar de un adulto.…”
unclassified
“…Facial expressions are phylogenetically ancient and shared across many non-human primate species 4 . In humans, facial expressions are universally performed across disparate societies and while perceptions of some emotions show cross-cultural variation 5 , within cultures, facial expressions are recognisable displays of emotional states 6 .…”
Section: Introductionmentioning
confidence: 99%